The Transition to a New Educational Culture - Exploring Possibilities - A Case Study in Iraq - AL-SAMMARRAEE, DUNYA SAAD (2022)
The e-portfolio has become widely used by many educational institutions in the world, and it has been acknowledged for its numerous benefits. The purpose of this study is to explore the readiness of a private university in Iraq to use the e-portfolio platform as a new technology tool for the first time; and to analyze its level of acceptance among the management team, teachers, and students. This case study was carried out at a private university in Baghdad, Iraq during the last semester of the academic year 2021-2022. A qualitative research design was used to gain insights into how technology particularly e-portfolio is perceived at the university. One-on-one and focus group interviews were used as instruments to collect data from ten participants, the Head of ICT, ICT Assistant, Administrator, two teachers, and five students. It was found that students were eager to use the e-portfolio and had perceived its potential value in their academic learning, but some require support and training because they have different IT skills. It was also revealed that the factors contributing to the success and acceptance of the new e-portfolio technology resemble understanding the benefits of the tool and its actual use. Lastly, the management team and teachers positively perceived the idea of e-portfolios but were not ready enough for a technological change due to certain constraints, but they aim for the change to happen one day. The study had some limitations which were treated according to what was found in the literature about such cases. Each point of limitation was justified under its respective section in the research paper. This study is important because it is an attempt to respond the need for the education system in Iraq to be in line with the global Ed-tech revolution and it is the first research paper exploring the e-portfolio tool in Iraq.